Quantifying the light absorption and source attribution of insoluble light-absorbing particles on Tibetan Plateau glaciers between 2013 and 2015 - X. Wang; H. Wei; J. Liu; B. Xu; M. Wang; M. Ji; H. Jin (The Cryosphere, 2019)
The deposition of insoluble light-absorbing particles (ILAPs) on snow and ice surfaces can significantly reduce albedo, thereby accelerating the melting process. In this study, 67 ice samples were collected from seven glaciers located on the Tibetan Plateau (TP) between May 2013 and October 2015. The mixing ratios of black carbon (BC), organic carbon (OC), and mineral dust (MD) were measured with an integrating sphere/integrating sandwich spectrophotometer (ISSW) system, which assumes that the light absorption of MD is due to iron oxide (Fe). Our results indicate that the mass-mixing ratios of BC, OC, and Fe exhibit considerable variability (BC: 10–3100 ng g−1; OC: 10–17 000 ng g−1; Fe: 10–3500 ng g−1) with respective mean values of 220±400 ng g−1, 1360±2420 ng g−1, and 240±450 ng g−1 over the course of the field campaign. We observed that for wavelengths of 450–600 nm, the measured light absorption can be largely attributed to the average light absorption of BC (50.7 %) and OC (33.2 %). Chemical elements and selected carbonaceous particles were also analyzed for source attributions of particulate light absorption based on a positive matrix factorization (PMF) receptor model. Our findings indicate that on average, industrial pollution (33.1 %), biomass or biofuel burning (29.4 %), and MD (37.5 %) constitute the principal sources of ILAPs deposited on TP glaciers.